Treatment Outcome and the Genetic Characteristics of Acute Promyelocytic Leukemia in Children in Poland From 2005 to 2018 - Małgorzata Czogała; Małgorzata Czogała; Katarzyna Pawińska-Wa̧sikowska; Katarzyna Pawińska-Wa̧sikowska; Teofila Ksia̧żek; Teofila Ksia̧żek; Barbara Sikorska-Fic; Michał Matysiak; Anna Rodziewicz-Konarska; Alicja Chybicka; Jolanta Skalska-Sadowska; Jacek Wachowiak; et al. (Frontiers Media S.A., 2020)
Background: The aim of the study was to analyze the treatment outcome and genetic characteristics of acute promyelocytic leukemia (APL) in children in Poland from 2005 to 2018.Methods: All 41 patients diagnosed with APL in Poland during the analysis period were eligible for the study. In period I (2005-2015), 33 patients were treated with chemotherapy and all-trans retinoic acid (ATRA), and in period II (2015-2018), 3 patients (high risk) received induction chemotherapy with ATRA and arsenic trioxide (ATO), and 5 patients (standard risk) received ATRA and ATO without chemotherapy.Results: Probability of 5-years overall survival (OS), event-free survival (EFS), and relapse-free survival (RFS) was 0.819 ± 0.069, 0.831 ± 0.063, and 0.961 ± 0.037, respectively, in the whole cohort. Four (11%) early deaths were observed. One patient died of severe infection in the course of disease progression. Relapse occurred in one patient, who died finally because of disease progression. All events occurred in the patients from period I. Variant APL was identified in one patient (successfully treated with chemotherapy with ATRA) and complex translocation in one patient (the only patient with relapse). Additional chromosomal aberrations were found in 26% of patients and FLT3-ITD mutation was detected in 44% of patients; none of those changes influenced clinical outcome.Conclusion: Treatment outcome in the analyzed group is similar to the results reported by other study groups. The main cause of death was coagulation disorders in the early stage of disease. Early, accurate diagnosis followed by specific treatment enables the reduction in the number of early deaths.